Miliary tuberculosis in an Indian lady: Looking beyond miliary tuberculosis - Arjun Lakshman; Varun Dhir; Narender Kumar; Manphool Singhal (Lung India, 2015)
Presence of miliary shadows in chest imaging in the appropriate clinical setting is often taken as a marker of miliary tuberculosis. If sputum is negative for acid -fast bacillus, empirical anti-tubercular therapy is given without securing a histological or microbiological diagnosis. We report a young female with human immunodeficiency virus infection who had miliary infiltrates on chest radiography. She was started on empirical anti-tubercular therapy. But an alternate diagnosis was achieved later with invasive sampling and ATT was stopped. This case illustrates the need for physicians to remain alert to diseases which mimic tuberculosis in presentation.